The Effect of a Training Program to Develop Speed Endurance and (YOYO) Test for Football Referees Level 2 - Abd, Kadgim; Kadhim, Ahmed (Journal of Physical Education, 2016)
The problem of this study comes as a result to the need of new updated training program to help football referees developing a high level of fitness during matches. Referees are expected to be physically well prepared in order to endure long time matches with continuous running in up and down speed. However, they are still randomly prepared based on their own potentials and general information in Training Science. Hence the need to double the efforts and set new training program to help passing the new referees’ (Yoyo) test updated by the International and the Asian Federation. The researcher has used the experimental method of one group style. The subject includes (15) football referees (level 2) out of (25) rated 60% of the original community. The tests used are (shuttle running 25x8), (30 m speed), and (YOYO) test. The conclusions have confirmed the positive role of the training program: 1) on the development process and the improvement of the referees’ physical abilities (speed and speed endurance); 2) on passing (YOYO) tests for almost all the referees.The researcher finally has recommended: 1) the central Referees Committee in Iraqi Federation to depend on specialized coaches in training or fitness. 2) to conduct regular training whether weekly or (3-4) times per week to raise the physical abilities of the referees